Nutritive characterisation of shrubs browsed by goats during summer in the north-west of Tunisia - Boubaker A.; Kayouli C.; Buldgen A. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
In vitro fermentation of six shrubs (Erica arborea, Phyllerea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber and Vibernum tinus) mostly browsed in summer was investigated using a closed fermenter and compared with common hay. The effect of PEG 4000 or feed block addition on in vitro fermentation of selected diet was studied. Diet was simulated using direct observation method results. Four goats receiving 500 g hay and 250 g concentrate twice a day were used as donors of rumen content. The browsed species were relatively low in crude protein and high in fibre. Values of pH and NH3 revealed satisfactory fermentation conditions. There were differences in gas production after 72 h. V. tinus produced the highest volume. The lowest gas production was obtained with Q. suber. All shrub species showed less fermentation activity than hay. Polyethylene glycol (PEG) addition led to a significant increase of gas production. The effect of feed blocks supply was low compared with PEG addition.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)